Daily behavior and interaction of cats (Felis catus) with humans at a canteen in IPB University - LIZA MAHERA; ASTUTI LATIF; SITI SARI AZYATI; HANNY RAMADHANTI; KANTHI ARUM WIDAYATI (Jurnal Natural, 2023)
Understanding feral cat behavior can be one of the aspects that is necessary for proper management and taking policy action in controlling the cat population. This study aimed to observe the daily activities of feral cats and see the correlation between the number of visitors on cat-to-human interaction at a canteen in IPB University. Observation of cat’s daily behavior was conducted by scan sampling method and cats’ interaction with humans was conducted by ad libitum sampling. Our results showed that self-care (66.27%) dominated the daily behavior of cats followed by negative behavior (20.83%) and affiliative behavior (12.9%). Correlation test showed there was a significant negative correlation between the number of visitors and frequency of affiliative behavior (p = 0.024). The number of visitors also shows a positive correlation to self-care (p = 0.034). No significant correlation between the number of visitors and negative encounters behavior (p = 0.27). The highest frequency value of cat-human interaction was approaching human (A) 28.15%, followed by vocalization (MV) 28.15% and eye contact (KM) 22.71%. Cat-human interaction behavior did not significantly correlate with the number of visitors (p 0.05). Our result implies that the feral cat’s use the canteen as a place to rest, not a place to find food and daily activities and human-cat interactions were specific for each study site. Therefore, in the management of feral cats, it was necessary to pay attention to the conditions of their respective habitats.